Hydrodynamic processes at the water-sediment interface of streambeds - Detert, Martin (Dissertationsreihe am Institut für Hydromechanik der Universität Karlsruhe / Universität Karlsruhe (TH), Institut für Hydromechanik, 2008)
Simultaneous 2D pressure and 2D velocity information at the rough water-sediment interface of streambeds were gained by a newly developed measurement setup. In the bed the pressure fluctuations decay exponentially within the first 1-2 equivalent sand roughnesses. Structural findings concerning coherent flow structures are consistent with models originally developed for smooth walls. A significant bed destabilizing flow-pressure pattern was identified for the first time.